My life as a radical Jewish woman : memoirs of a Zionist feminist in Poland - Raḳoṿsḳa, Puʻah, 1865-1955 (Modern Jewish experience (Bloomington, Ind.), 2002)
In this striking autobiography, Puah Rakovksy (1865-1955) tells of her experiences as a Jewish woman in later 19th- and early 20th-century Poland who broke with her traditional upbringing to become a professional educator, Zionist activist, and feminist leader. Her passionate account offers unprecedented entree into the life experience of East European Jewry in a period of massive social change.